Pathology of Organizational Training in Universities of Iran Medical Sciences based on McKinsey 7S Mode - Fahimeh Rabbanikhah; Robabeh Mousa Gholizadeh; Samira Alirezaei (Shahid Sadoughi University of Medical Sciences, 2017)
Background: The educational system of any organization is actively and potentially one of the most important aspects of that organization in human resource development. It is necessary for any system to benefit pathology in order to function properly. The goal of this study is to investigate and identify the weaknesses of staff education systems of the country's medical universities based on McKinsey 7S Model. Methods: This cross-sectional study was conducted in two phases. In the first phase through key criteria, seven elements of the model were extracted using expert ' opinions and selection criteria was converted to measures and distributed in the form of a questionnaire among 113 officials and experts from Medical Sciences universities. Cronbach's alpha questionnaire was 0.931. Data were analyzed by using descriptive statistics for the frequencies of demographic data and means and standard deviation and analysis statistics such as t-test. Results: The results showed that the state of education in the country's universities is undesirable respectively in dimensions of the structure (P-value = 0.401), management practice (P-value = 0.69) and strategy (P-value = 0.473). However, the average of overall pathology (141.07) was higher than the interested average (138) and showed that there is generally no serious damage in the country's medical universities training. Conclusion: Managers' support, clarification of educational rules and regulations, determining specific hierarchy in training unit, goal setting and training strategies in a targeted form and by stakeholders' engagement are proper strategies to remove injuries in staff training systems.